Le tabellionage normand : du sceau à la signature ? Pour une étude des signes de validation pendant le règne de Charles V (1364-1380) - Claude Jeay (Tabularia)
The majority of the tabellions of the royal jurisdictions in Normandy are undeniably influenced by the chancellery of the King of France, when they need to adopt an paraph, while others, on the contrary, are original. In any case, the choice of the paraph is not insignificant, but combines graphic possibilities, brand identity and symbolic dimension. This abundance reflects the dynamism of the king in the Norman province, proof of the influence of royal power, whose visible manifestations are thus multiplied.